Biological properties of T6S cells, a clone of burn-associated type 2 T cells - Nakajima, N; Utsunomiya, T; Kobayashi, M; Pollard, R B; Suzuki, F (Nihon Rinshō Menʾeki Gakkai kaishi, 1999)
A clone of type 2 T cells (T 6 S cell) was established from burn-associated CD 8+ CD 11 b+ TCR gamma/delta + type 2 T cells, and their biological properties were examined. After stimulation by anti-CD 3 monoclonal antibody (mAb), T 6 S cells produced IL-4 and IL-10 into their culture fluids. However, IFN-gamma and IL-2 were not demonstrated in the culture fluids of T 6 S cells stimulated with the mAb. The susceptibility of thermally injured mice to infection with herpes simplex virus type 1 (HSV-1) or Candida albicans (C. albicans) has been shown to be approximately 50 (C. albicans) to 100 (HSV-1) times greater than that of normal mice. As compared with the resistance of thermally injured mice to these pathogens, mice inoculated with 1 x 10(6) cells/mouse of T 6 S cells (designated as T 6 S-mice) showed the same susceptibility to the infections. When T 6 S-mice treated with a mixture of monoclonal antibodies (mAbs) directed against IL-4 and IL-10 were infected with a lethal dose of HSV-1 or C. albicans, their resistance to these pathogens was restored to levels found in normal mice. From the experiments using T 6 S-mice, it is suggest that type 2 T cells or their cytokine products (IL-4 and IL-10) may play an important role on the impaired resistance of thermally injured mice to certain opportunistic pathogens. T 6 S cell may be a useful tool to study opportunistic infections in hosts bearing type 2 T cells.